Problematising resilience: development practice and the case of Palestine. Issue 4 (18th May 2020) - Keelan, Emma Patricia; Browne, Brendan Ciarán
ABSTRACT: This article considers the rapid rise of a resilience discourse in relation to its application in humanitarian and developmental aid in Palestine. In Palestine, the term resilience has permeated the operational policy of leading NGOs. The article argues that uncritical application of the language of resilience is deeply problematic in places such as Palestine where the asymmetrical nature of the conflict is sustained by international political inertia, significant aid dependency, and intersectional and multi-layered conflict experience. Adopting a resilience discourse simultaneously embeds the colonial nature of conflict in Palestine and maintains the status quo rather than agitating for change.